If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8n + -11 = 6x + 3 Reorder the terms: -11 + 8n = 6x + 3 Reorder the terms: -11 + 8n = 3 + 6x Solving -11 + 8n = 3 + 6x Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 8n = 3 + 11 + 6x Combine like terms: -11 + 11 = 0 0 + 8n = 3 + 11 + 6x 8n = 3 + 11 + 6x Combine like terms: 3 + 11 = 14 8n = 14 + 6x Divide each side by '8'. n = 1.75 + 0.75x Simplifying n = 1.75 + 0.75x
| 2=a-1 | | b-1=10 | | t-5=-7 | | -5w=-35 | | a+1=-3 | | 1+t=5 | | -2w=22 | | 10=w+4 | | -11=t-4 | | 4+n=9 | | -6m=-48 | | 10x/-2y | | 4=d+1 | | 6+k=6 | | 21=m+10 | | -63x^2-23x+56= | | 7k=-84 | | -9+t=-8 | | 9+w=11 | | -4+w=-2 | | n+10=-1 | | 2.3/3.8 | | 7+m=16 | | b-3=-1 | | 2d=20 | | a-9=-8 | | 5y-3x+1=0 | | 6x^2+kx-50=0 | | -4t=-24 | | 9+m=20 | | d-6=-6 | | d+10=20 |